December to Remember a Novel - Bayliss, Jenny (New York G. P. Putnam's Sons, 2023)
"Wildly different half-sisters Maggie, Simone, and Star have hardly seen each other since their sprightly summers at Rowan Thorp, their eccentric father Augustus's home. Known for the fruitful ways in which his bustling knick-knack shop kept the tired town afloat, Augustus was loved by all and known by none, not even his daughters. Now, years later, the three estranged women are unexpectedly reunited at the reading of Augustus's will. Maggie, Simone, and Star are shocked to find out that Augustus has engineered a series of hoops through which the three women must jump to unlock their inheritance--the last thing any of them want to do. But Maggie and Star desperately need the money. And who would Simone be to resist? Through hilarious goose chases, community mishaps, and one heart-warming winter solstice celebration, love, hope, and reconciliation is in the air, if only the three sisters can let themselves grasp it" --
Includes discussion questions (page 398-399).
112290
Keywords: Sisters; Fathers -- Death; Estranged families; Inheritance and succession; Domestic fiction; Christmas fiction; Novels